1992
DOI: 10.1029/92wr01007
|View full text |Cite
|
Sign up to set email alerts
|

Regional geohydrologic‐geomorphic relationships for the estimation of low‐flow statistics

Abstract: Many investigators have sought to develop regional multivariate regression models which relate low-flow statistics to watershed characteristics. Normally, a multiplicative model structure is imposed and multivariate statistical procedures are employed to select suitable watershed characteristics and to estimate model parameters. Since such procedures have met with only limited success, we take a different approach. A simple conceptual stream-aquifer model is extended to a watershed scale and evaluated for its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
303
2
9

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(323 citation statements)
references
References 17 publications
9
303
2
9
Order By: Relevance
“…This suggests that the MS, CE, and CH methods are overestimating the baseflow recession constant in the study area. In general, the baseflow recession constant ranged from 0.75 to 0.95 [14,33]. The recession constants of CR, AR(1), and VK methods fell within this range, whereas the recession constants of MS, CE, and CH were larger.…”
Section: Applicability Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that the MS, CE, and CH methods are overestimating the baseflow recession constant in the study area. In general, the baseflow recession constant ranged from 0.75 to 0.95 [14,33]. The recession constants of CR, AR(1), and VK methods fell within this range, whereas the recession constants of MS, CE, and CH were larger.…”
Section: Applicability Assessmentmentioning
confidence: 99%
“…In this study, the mean value of the recession constants calculated from the AR(1) model was set to represent the recession constant of one forest catchment. When the streamflow is linearly related to the basin storage, Vogel and Kroll [14] calculated the recession constant with model error additives in log space. The baseflow recession constant is determined using the least squares method as follows:…”
Section: Cheng Methods (Ch)mentioning
confidence: 99%
See 2 more Smart Citations
“…Under strong assumptions, he found that the outflow from an aquifer with a concave floor had the form Ce -αt , with C being an arbitrary value depending on the initial conditions and α (generally known as recession coefficient) a positive constant dependent of the geometric configuration of the aquifer and its hydraulic conductivity. During the years, exponential decay relationships of the same type Q ~ e -αt were derived by Maillet (1905), Horton (1933), Nathan and McMahon (1990), Vogel and Kroll (1992), Brutsaert (1994), Shevenell (1996), Long and Derickson (1999), among others. Different approximations have also been proposed considering inclined aquifer floor, as proposed by Boussinesq (see Eq.…”
Section: Introductionmentioning
confidence: 99%